An update on the safety of apremilast for the treatment of plaque psoriasis. Issue 4 (2nd April 2020) - Shavit, Eran; Shear, Neil H.
ABSTRACT: Introduction : Apremilast is an oral phosphodiesterase inhibitor, approved for moderate to severe psoriasis in adults. Despite the advancement in dermatology, and the introduction of newer biological drugs, apremilast this is the only novel oral medication that has been introduced to treat psoriasis in the past two decades. Like additional other more traditional oral medications, its advantages and disadvantages should be discussed and compared within this group of oral-systemic medications. Area covered : We conducted a review to assess the safety, efficacy, and adherence of apremilast for psoriasis treatment. The aim of this paper was to provide an overview of apremilast regarding its mechanism of action, indications, and adverse events. Expert opinion : Apremilast has been found to be a safe and efficacious drug for moderate-to-severe psoriasis, and despite minor numerous side effects, most of the patients adhere to the therapy. Therefore, overall, it may be easily embraced as the drug of choice for this category. However, for more severe psoriasis cases newer biological drugs seem to be superior to apremilast.